Bridging Worlds: Integrating Indigenous Knowledge Systems With Science Education. A Case of the Lubombo Region Schools - Claretah, Makuvire; Penias, Chikuvadze; Nokulunga, Dladla (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
This study explores the intersection of indigenous knowledge systems and science education within the context of Eswatini. The study objectives include: examining indigenous knowledge's influence on child development and academic achievement, identifying integration challenges and opportunities, assessing educators' perceptions and recommending sustainable implementation strategies. The study employed an exploratory case study design. Data was collected from ten schools in Libombo region using questionnaires, focus group discussions, observations and document analysis targeting principals, teachers, and students. Thematic analysis and descriptive statistics were used to analyse the data. Findings show indigenous knowledge positively influences child development and academic achievement promoting holistic learning cultural identity and engagement. Challenges include lack of documentation of indegenous knowledge systems and cultural sensitivity while opportunities include authentic integration of cultural heritage. Recommendations include enhancing digital infrastructure providing educator professional development and developing educational content incorporating local language and culture in science education. The study concludes that the intergration of culture and science creates an educational system which honours cultural heritage while preparing students for future challenges. Ongoing teacher professional development is highly encouraged